History of loot and stolen art : from antiquity until the present day - Lindsay, Ivan (Unicorn Press Ltd, 2014)
The author of this enthralling book aims to present a well-illustrated and documented alternative history of the Western World through graphic accounts of looting and art theft from the time of Sargon, ruler of Syria in 721 BC, to the present day. Almost all the principal players included appear on the stage of World history and many of them are known as conquerors, confiscators (the old-fashioned word for looters) and ruthless administrators of the regions they created as a result of their ...